The effectiveness of cannabidiol in the treatment of anxiety disorders: An integrative literature review (Research, Society and Development, 2024)
The objective was to report the effectiveness of the use of cannabidiol (CBD) in the treatment of anxiety disorders, as neuroimaging investigations in humans indicate that its action occurs in limbic brain areas, associated with anxiety. The lack of control over the doses and amount of cannabidiol used was analyzed to understand its mechanism in patients with anxiety. It is an integrative review study, collecting articles from the following platforms: Latin American and Caribbean Literature in Health Sciences (LILACS) and U.S. National Library of Medicine (PUBMED). To maintain the theme and support the article, the descriptors “cannabidiol”, “cannabidiol”, “treatment”, “anxiety disorders”, “anxiety disorders” and “CBD” were used. As inclusion criteria: published articles in the last 5 years, free access and as exclusion criteria therapy studies combined with tetrahydrocannabinol (THC) and animal analysis. The therapeutic potential of cannabidiol in the treatment of anxiety was observed with a favorable safety profile; action in facilitating extinction of fear and reduction of present fearful behaviors; in addition to oral CBD administered in a corn oil formula without the bioconversion of tetrahydrocannabinol(THC), contrary to recent studies. It is concluded that cannabidiol acts as a modulator of inflammatory processes in addition to reducing oxidative stress, emerging as a less harmful alternative compared to conventional treatments for anxiety disorder, however its use in the treatment of anxiety disorder still requires more research with a more cautious approach.